Influence of contrast injection flux on the outcome of the angiotomography for the diagnosis of pulmonary embolism (Brazilian Journal of Radiation Sciences, 2021)
With the development of computed tomography, tomography examinations have been replacing other modalities of imaging tests. Computed tomography angiography to pulmonary thromboembolism, for example, has been replacing pulmonary scintigraphy of ventilation/perfusion and angiography of pulmonary vessels. But angiotomography to the pulmonary thromboembolism is a complex examination, where factors such as scanning time, contrast injection flow, venous access caliber, venous access puncture site, use of the contrast injector, auto-trigger parameters, among others, interfere in the outcome of exam in the studied population. In this study, we performed the contrast ratio (RZC), relative the opacification of contrast in the trunk of the pulmonary artery and the descending aorta, which may vary according to the injection protocol used, determined by the flow of contrast injection (ml/s) associated with the auto-trigger (HU) parameters of the density reading in automatic mode of the equipment. For the injection of manual contrast, and its mean and standard deviation of RZC (2.66±3.56), for the flow (ml/s) and automatics reading (HU) protocols the means and standard deviations RZC consecutively are: 3.5 ml/s and 90 HU (3.68±2.79); 3.5 ml/s and 70 HU (1.90±0.72); 4.0 ml/s and 70 HU (1.98±0.56); 3.0 ml/s and 80 HU (2.15±0.89); 3.5 ml/s and 80 HU (1.50±0.36); 4.0 ml/s and 80 HU (3.91±3.22); 4.5 ml/s and 80 HU (4.69±4.82); 5.0 ml/s and 80 HU (4.27±3.78). The technique with the best result in the average level of RZC was the one that used a flow of 4.5 ml/s and auto-trigger in 80 HU.
Keywords: computed tomography; Computed tomography angiography for TEP; Flux; Contrast ratio; Dose optimization